2018
DOI: 10.2215/cjn.08600817
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Center Patient Navigator and Access to Transplantation among High-Risk Population

Abstract: Background and objectives Barriers exist in access to kidney transplantation, where minority and patients with low socioeconomic status are less likely to complete transplant evaluation. The purpose of this study was to examine the effectiveness of a transplant center-based patient navigator in helping patients at high risk of dropping out of the transplant evaluation process access the kidney transplant waiting list.Design, setting, participants & measurements We conducted a randomized, controlled trial of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 44 publications
0
56
0
1
Order By: Relevance
“…Testing of mediation of SES, comorbidity, or SES and comorbidity on listing for kidney transplant within 1 year between black versus white patients with kidney failure (n53013) or receipt of transplant between black versus white kidney transplant candidates on the waitlist (n52068), using inverse odds ratio weighting and among a population who have started the transplant evaluation process disparities (4,(6)(7)(8)(9). It is at this point that transplant centers engage with candidates and have opportunities to influence the coordination of the transplant process (18,30). Our observed disparity in listing of 0.76 is consistent with studies among referred patients, where observed racial disparities ranged from 0.52 to 0.88 (10,11,13,16).…”
Section: Discussionmentioning
confidence: 99%
“…Testing of mediation of SES, comorbidity, or SES and comorbidity on listing for kidney transplant within 1 year between black versus white patients with kidney failure (n53013) or receipt of transplant between black versus white kidney transplant candidates on the waitlist (n52068), using inverse odds ratio weighting and among a population who have started the transplant evaluation process disparities (4,(6)(7)(8)(9). It is at this point that transplant centers engage with candidates and have opportunities to influence the coordination of the transplant process (18,30). Our observed disparity in listing of 0.76 is consistent with studies among referred patients, where observed racial disparities ranged from 0.52 to 0.88 (10,11,13,16).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent trial that found that involvement of a transplant center-based navigator did not significantly improve access to waitlisting among disadvantaged patients referred to a single transplant center. In that study, the navigator was a transplant social worker and made an average of about nine contacts with each patient (25). Moreover, the new waiting list allocation system, which counts time from start of dialysis rather than from listing, may make efficient workups less important (26).…”
Section: Discussionmentioning
confidence: 99%
“…The foundation of any good living donor program is outreach, so Georgia recently tested the effectiveness of a program whereby trained kidney transplant recipients serve as patient navigators for patients with end‐stage kidney disease within dialysis facilities. This strategy increased patient referrals to a transplant center when combined with other educational interventions . The Emory Transplant Center has tested a social worker navigator intervention targeting mostly African‐Americans, and patients assigned a navigator experienced a higher number of living donor inquiries.…”
Section: The Solutionsmentioning
confidence: 99%